Laboratory investigation of the influence of fractures on CO2 flooding - Qing-Fu, Zhang (Frontiers in Earth Science, 2022)
CO2 injection is a promising method for low permeability reservoirs. CO2 is much easier to be injected into underground compared with water. The solubility of CO2 in oil decreases the oil density and viscosity, leading to enhancing the oil recovery. CO2 flooding could achieve the dual purpose of developing oil effectively and reducing greenhouse gas. Therefore, this technique has both economic and social benefits and is an essential technology to achieve green development. Nature fractures are widely developed in low permeability reservoirs and artificial fractures are often used to improve the oil development. These fractures have a significant influence on flow patterns during CO2 flooding. In addition, fracture is also one of key factors of CO2 channeling. Therefore, the influence of fracture on CO2 flooding pressure distribution, fluid composition and displacement efficiency needs to be studied. In this work, CO2 flooding experiment is implemented to test the pressure distribution and outlet composition changes during CO2 flooding under different fracture lengths and aperture. The experiment shows that the long and wide fracture can effectively reduce the injection-production pressure difference. However, the fracture also has negative effect on oil development. Fracture length and aperture have a significant effect on the gas phase composition at the outlet, but has little effect on the oil phase composition.